engaruh Kecerdasan Emosional Dan Lingkungan Kerja Terhadap Kinerja Guru Sekolah Menengah Kawung I Surabaya - asjari, fachrudy (Fakultas Ekonomi Universitas PGRI Adi Buana, 2013)
Background This research intended to asses the emotional intelligence, work environment to the performance which must be performed to the senior high school teacher in Surabaya. Method This research was conducted in Surabaya which covered ....teachers as respondent. This research by utilizing Regression, the technique was processed with SPSS 11.0 to analyze some hypothesis. The intercorrelations models between two variables in this study revealed that the hypothesis have significant correlation. Conclusion. The result of this research were empirical date of the development of the theoretical of human resoureces and practice management.